2015
DOI: 10.1103/physrevb.91.245413
|View full text |Cite
|
Sign up to set email alerts
|

Portlandite crystal: Bulk, bilayer, and monolayer structures

Abstract: Ca(OH) 2 crystals, well known as portlandite, are grown in layered form, and we found that they can be exfoliated on different substrates. We performed first principles calculations to investigate the structural, electronic, vibrational, and mechanical properties of bulk, bilayer, and monolayer structures of this material. Different from other lamellar structures such as graphite and transition-metal dichalcogenides, intralayer bonding in Ca(OH) 2 is mainly ionic, while the interlayer interaction remains a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 51 publications
6
36
0
2
Order By: Relevance
“…8,9 However, the studies on single layer alkaline-earth-metal hydroxides (AEMHs) (i.e., Ca(OH) 2 and Mg(OH) 2 ) are sparse and have only started very recently. 11,12 Aierken et al investigated the structural, electronic, magnetic, vibrational, and mechanical properties of monolayer Ca(OH) 2 by rst-principles calculations. The results show that Ca(OH) 2 can be isolated in monolayer form and it is a direct bandgap semiconductor independent of the number of layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 However, the studies on single layer alkaline-earth-metal hydroxides (AEMHs) (i.e., Ca(OH) 2 and Mg(OH) 2 ) are sparse and have only started very recently. 11,12 Aierken et al investigated the structural, electronic, magnetic, vibrational, and mechanical properties of monolayer Ca(OH) 2 by rst-principles calculations. The results show that Ca(OH) 2 can be isolated in monolayer form and it is a direct bandgap semiconductor independent of the number of layers.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that Ca(OH) 2 can be isolated in monolayer form and it is a direct bandgap semiconductor independent of the number of layers. 12 Besides, monolayer gray arsenic (arsenene), a new elemental 2D semiconducting material with buckled honeycomb lattice, has been recently proposed and was predicted to be kinetically very stable based on the theoretical calculations. [13][14][15][16] It is also found that the arsenene is an indirect-band-gap semiconductor and undergoes an indirect-to-direct band-gap and semiconducting-to-metallic transitions under external electric elds or strains.…”
Section: Introductionmentioning
confidence: 99%
“…Aer a decade of research which was triggered by the synthesis of graphene, 1 the theoretical prediction and synthesis of many 2D ultrathin materials such as silicene, 2,3 germanene, 2,4,5 stanene, 6,7 transition metal dichalcogenides (TMDs), [8][9][10][11][12][13][14][15] hexagonal III-V binary compounds (h-BN, h-AlN) [16][17][18][19] and metal hydroxides (Ca(OH) 2 , Mg(OH) 2 ) 20,21 have been achieved. However, recent research efforts have been directed towards not only the synthesis of graphene-like materials, but also towards the functionalization of existing ultra-thin crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Structure and Stability of Portlandene Few-layered Ca(OH) 2 crystals have already been successfully synthesized at ambient conditions. 23 Here, we start our analyses by showing that monolayer portlandene corresponds to a local energy minimum on the Born-Oppenheimer surface using various stringent stability tests. The optimized geometrical parameters of the monolayer structure are presented in Figure 1(a).…”
Section: Pacs Numbersmentioning
confidence: 99%